Peran Social Brand Engagement Dan Product Quality Terhadap Peningkatan Brand Awareness, Brand Association, dan Purchase Intention - Rachmanu, Edvian Ditya; Purnomo, Fajrin; Hartini, Sri (Jurnal Ilmu Manajemen, 2024)
Social brand engagement is essential in the current digital era because interactions between brands and consumers occur conventionally and involve social media, which is the center of public attention. Social media is an interactive platform for customers to interact and engage with other people and brands during various process stages. This research examines the influence of social brand engagement and product quality on brand awareness, brand association, and purchase intention. The study used quantitative methods; primary data was obtained from 116 respondents who are members of the Basketball Lovers Community on Twitter (aged 18–40 years) using Partial Least Square (PLS) as a data analysis technique. The results of this research indicate that Brand Association and Brand Awareness do not significantly influence Purchase Intention. On the other hand, it was found that Product Quality significantly influences Purchase Intention. Apart from that, the research results also show that Product Quality significantly influences Social Brand Engagement. Social brand engagement also plays a vital role in influencing brand association and awareness. This research provides an in-depth understanding of the factors that influence Purchase Intention, emphasizing the critical role of product quality in shaping consumer preferences and the positive contribution of social interactions in building associations and brand awareness.